Rapid fabrication of nanoneedle arrays by ion sputtering - Huang, Y; Cockayne, D; Ana-Vanessa, J; Cowburn, R; Wang, S; Ward, R (2008)
We report a novel method for rapidly fabricating ordered nanoneedles using an ion beam that cuts through the Fe/GaAs single thin layer or the Fe/MgO/Fe/GaAs multilayer producing a pillar pattern followed by raster-scanning normal to the patterned area. However, such ordered nanoneedles were not formed on the pure GaAs substrate surface without the thin Fe film coating, nor were nanoneedles formed on the GaAs substrate coated with a thin Cr epitaxial film, when this method was used. It has advantages over other methods, being simple, fast and well controlled for fabricating one-dimensional nanostructure arrays, leading to a range of applications such as high aspect ratio sharp tips for atomic force microscope/atom probes and consequent possible quantum confinement effects or arrays of nanostructures for field-optical/photoluminescence emission and data recording. © IOP Publishing Ltd.